Vaccination situation against Covid-19 in the quilombola population of brazilian northeast states (Research, Society and Development, 2022)
The study aims to characterize the situation of vaccine coverage in the fight against Covid-19 in the quilombola population of the northeastern Brazilian states. This is a descriptive study with a quantitative approach, data collection was carried out through the Covid-19 Vaccinometer of the Ministry of Health obtained through the National Health Data Network (RNDS). The sample consisted of data referring to vaccine coverage of the first dose, second dose, first and second booster vaccine against Covid-19 in the quilombola population in Brazil between 2021 and September 2022. Data analysis was performed through the tabulation of data using Excel program (2017). It was found that no state managed to reach the indicator recommended by the Ministry of Health, which is vaccination coverage above > 90%. Pernambuco is one of the states that best presented vaccine coverage related to dose 1 (85.3%), followed by the states of Maranhão (69.2%), Bahia (51.3%) and Ceará (51.5%). The states of Alagoas, Rio Grande do Norte and Sergipe proved to be a challenge to apply the Covid-19 vaccine in the quilombola population, according to unfavorable indicators in all doses of the vaccine.